Psychologic interventions in patients with the chronic dermatologic itch in atopic dermatitis and psoriasis: A step forward with family constellations seminars - Capec, Szergej; Petrek, Martin; Capec, Gabriella; Yaremkevych, Roman; Andrashko, Yuriy (Frontiers in Medicine, 2022)
Chronic itch is a complex psychophysiological sensation, which can severely affect the quality of life in patients with atopic dermatitis and psoriasis. Itch depends on the irritation of receptors in the skin and the processing of sensory information in the central nervous system. Severe itch leads to activation and later on to disruption of the stress response, resulting in disorders of skin repair, functional and microstructural changes in the areas of the central nervous system that are responsible for the perception of itch. Psychosocial stress can be an essential factor, activating neurohumoral mechanisms which lead to increased itch and scratch, exacerbating skin damage. Patients with chronic itch often have sleep disorders, increased irritability, and depletion of the nervous system. They are characterized by disrupting social relationships, high incidence of anxiety, depressive disorders, and suicidal tendencies. Psychological methods of intervention can effectively influence various mechanisms in the pathogenesis of itch and scratch and improve social functioning in patients with chronic dermatological itch. In this mini-review, we discuss family constellation seminars as an effective method of psychological intervention that can reduce the intensity of itch, and improve sleep and performance in patients with atopic dermatitis and psoriasis. This method is insufficiently described in previous reviews of psychological interventions in atopic dermatitis and psoriasis patients. The positive impact of family constellations seminars in patients with chronic dermatological itch may be related to reducing stress by improving understanding of the family situation, appropriate management of family secrets, and enhancing interactions with the social environment.